Stock Performance Prior to Federal Holidays - Boylan, Daniel; Albertson, Nikolas L.; Cline, Jeffrey (Journal of Applied Business and Economics, 2023)
The purpose of this study is to understand the impact of Federal holidays on a stock price. This research analyzed stock performance for the five trading days before each of the ten Federal holidays. Forty data points are found by the difference between a buy price (six days before a holiday) and a selling price (one day before a holiday). A 95% confidence interval is calculated using the difference of two sample means of the buy and sell prices. The mean buy price and sell prices were different enough to show an investible opportunity. This shows Federal holidays impact stock prices.